2019
DOI: 10.1016/j.soilbio.2019.107529
|View full text |Cite
|
Sign up to set email alerts
|

Ants reign over a distinct microbiome in forest soil

Abstract: Biotic and abiotic characteristics shape the microbial communities in the soil environment. Manipulation of soil, performed by ants when constructing their nests, radically changes the soil characteristics and creates a unique environment, which differs in its composition, frequency and abundance of microbial taxa, from those in the reference soils. We sampled nests of the moundbuilding ant Formica exsecta, and the surrounding reference soils over a three-month period, and generated NGS (Illumina MiSeq), and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 93 publications
1
31
1
Order By: Relevance
“…In the context of those results, therefore, we cannot evaluate the structure of the nest-carton bacterial community identified here. Nevertheless, reports based on 16S sequencing have been published for nests of the Neotropical ants Azteca trigona and A. alfari, and the Palearctic species Formica exsecta (Lucas et al 2017(Lucas et al , 2019Lindström et al 2019). Three phyla (Proteobacteria, Actinobacteria and Acidobacteria) were the most abundant in the microbiota profiles determined in those studies; the same pattern emerged in the present study.…”
supporting
confidence: 82%
“…In the context of those results, therefore, we cannot evaluate the structure of the nest-carton bacterial community identified here. Nevertheless, reports based on 16S sequencing have been published for nests of the Neotropical ants Azteca trigona and A. alfari, and the Palearctic species Formica exsecta (Lucas et al 2017(Lucas et al , 2019Lindström et al 2019). Three phyla (Proteobacteria, Actinobacteria and Acidobacteria) were the most abundant in the microbiota profiles determined in those studies; the same pattern emerged in the present study.…”
supporting
confidence: 82%
“…To better understand variability between ant species in their susceptibility to pathogens, as well as how different pathogens affect the ant species, we investigated how two opportunistic pathogenic fungi ( Beauveria bassiana and Metarhizium brunneum ) affect the survival and behavior of twelve ant species from four different genera. The ant species were all common in the study area, which was characterized by the oligotrophic, moderately acidic soils that are typical of coniferous forests [34], as well as habitats consisting of pine and spruce stands, dry meadows, and lusher, grove-like patches [35]. Following exposure to the pathogens, we screened for three specific behaviors (autogrooming, allogrooming, trophallaxis), which previously have been associated with pathogen exposure (e.g., [20,21,22,24,36,37]).…”
Section: Introductionmentioning
confidence: 99%
“…Because of these differences, red wood ants' nest is a distinctly separate microenvironment, which may promote formation of a specific microbial community, different than those common for the surrounding forest litter or soil [47,48]. Such a phenomenon was observed for F. exsecta [24] (subgenus Coptoformica [34]). The study showed that F. exsecta mounds' core microbiomes differ from the microbiome of the surrounding soils, with Exophiala, Oidiodendron, Scleroconidioma, and Umbelopsis being core fungal indicators of the nest [24].…”
Section: Red Wood Ants' Mounds Are Very Specific Microenvironments Actively Shaped By Their Biocenosismentioning
confidence: 99%
“…were isolated [20,22]. Still, fungal species coexisting in nests and the surrounding environment of Holarctic ant species were investigated sparsely [23,24]. Lindström et al focused on F. exsecta nests' microbiome and showed that both composition and richness of the microbiome are unique in comparison to the reference soils [24].…”
Section: Introduction 1mutualistic Fungus-ant Interaction In the Holarctic Region Is Understudiedmentioning
confidence: 99%
See 1 more Smart Citation